Manajemen Koagulopati pada Pasien Covid-19 - Novita Anggraeni (Fakultas Kedokteran Universitas Riau, 2021)
The 2019–20 Coronavirus outbreak has been declared a Public Health Emergency of International Concern (PHEIC). Cytokine storms and impaired blood coagulation are frequently associated with Covid-19. Dysregulation of the coagulation cascade and interalveolar fibrin clot formation are prominent findings in coronavirus infection associated with severe respiratory disease and have been demonstrated in human and animal models. A 66-year-old woman with COVID-19 was consulted by the Anesthesia Department of the Arifin Achmad Hospital Pekanbaru for intensive care. The patient complained of shortness of breath since 4 days of SMRS. The patient had an elevated d-dimer. Anticoagulation may be considered in COVID-19 patients from the time of treatment until the patient's discharge (35-42 days).